Teaching English by Using Canva: Students’ and Lecturers’ Voice - Wijayanti, Erfin (ENGLISH FRANCA : Academic Journal of English Language and Education, 2022)
This research discovers students’ and lecturers’ voice on using Canva in English language teaching. This research employed quantitative descriptive method with 31 English Foreign Language (EFL) students and 5 lecturers. The data are gained from 31 students and 5 lecturers of English Department at IAIN Fattahul Muluk Papua. The students’ and lecturers are given a set of questionnaires to obtain their response on using Canva. After gaining the data, the researcher analysed the students’ and lecturers’ response by counting its frequency and percentage. The findings of this research Indicated that the majority of students and lecturers have positive voice on using Canva in English language teaching based on three indicators that is provided by researcher, those are: usefulness, ease to use, and easy access. This research revealed that Canva is usefulness tool for English language teaching. Canva is also ease of use tool for English language teaching which easy to use, effective, improve teaching and learning process, and easy to distribute. At the end, Canva has easy access because Canva provides everything for teaching and learning process such as video, images, colourful. Besides, Canva becomes an interesting App, and good choice for learning and teaching process.